Performance and Relative Incentive Pay: The Role of Social Preferences - Pablo Hernandez; Dylan B. Minor; Dana Sisak (Tinbergen Institute, 2013)
Under relative performance pay, other-regarding workers internalize the negative externality they impose on other workers. In one form -increased own effort reduces others' payoffs- this results in other-regarding individuals depressing efforts. In another form punishment reduces the payoff of other workers- groups with other-regarding individuals feature higher efforts because it is more difficult for these individuals to sustain low-effort (collusive) outcomes. We explore these effects experimentally and find other-regarding workers tend to depress efforts by 15% on average. However, selfish workers are nearly three times more likely to lead workers to coordinate on minimal efforts when communication is possible. Hence, the social preferences composition of a team of workers has nuanced consequences on efforts.
Keywords: D03; M50; J30; 330; Social Preferences; Relative Performance; Collusion; Leadership